Ringed seal (Pusa hispida) tooth annuli as an index of reproduction in the Beaufort Sea. (June 2017) - Nguyen, Linda; Pilfold, Nicholas W.; Derocher, Andrew E.; Stirling, Ian; Bohart, Alyssa M.; Richardson, Evan
Abstract: Multi-decadal time-series of biological indices that reflect the state of a population are rare in ecological studies, but invaluable for assessing environmental regulation of population dynamics. We utilized canine teeth extracted from ringed seals ( Pusa hispida ) killed by polar bears ( Ursus maritimus ) in the Beaufort Sea, Canada, in 1985–2011, to obtain widths of annual growth layers in the cementum. Canine teeth for 75 individuals were measured and compared across years using a proportional width index (PWI) spanning 1965–2007. PWI was positively correlated with ringed seal ovulation rate obtained independently from other studies and was significantly lower than normal during ringed seal reproductive declines in 1974–75, 1984–87, 1991–93, and 2004–05, suggesting that PWI reflects ringed seal reproductive capacity. The PWI was also examined against climatic and sea ice factors to assess environmental regulation of ringed seal reproduction. Results suggest that ringed seals benefit from cyclonic circulation regimes in the Beaufort Sea, and an earlier breakup of sea ice in summer that may positively influence the quality and quantity of food during the open water season. Results highlight how cementum annuli in the canine teeth of ringed seals can provide an index of body state and linkages to sea ice conditions. Canine teeth from ringed seals can function as a means to monitor the effects of past Arctic marine variability on area-specific populations for which there are few independent empirical data.